Effect of Herbal Syrup Linkus on Acute and Gross Toxicity and Electrolytes in Blood and Organs - Riffat Farooqui; Rafeeq Alam Khan; Tahira Zamir; Nasim Karim (Journal of Bahria University Medical and Dental College)
Objective: To evaluate the effect of herbal syrup Linkus on acute and gross toxicity and electrolytes level in blood and organs. Materials and Methods: This interventional study was carried out in the department of Pharmacology, Faculty of Pharmacy,University of Karachi after approval from BASR-KU. In this study twenty-eight healthy rabbits of either sex weighing 0.90 kg to 1.2 kg. All animals were equally divided into four groups, one served as control group while, remaining three groups received herbal syrup Linkus at three different doses. Acute toxicity was tested in mice by Lorke’s method whereas effect on gross toxicity, blood and organ electrolytes was evaluated in Rabbits. Results: Herbal syrup Linkus exhibited LD50 values greater than 5 gm / kg per 24 hrs. No gross toxicity and mortality was observed during the whole experimental period. Non significant changes were observed in blood and organ electrolytes (Calcium, Potassium and Sodium) level. Conclusion: Herbal syrup Linkus has produced no toxic effect at the administered doses neither showed any significant change in the electrolytes level in the blood and vital organs.